Lung transplantation despite preformed donor-specific antihuman leukocyte antigen antibodies: a 9-year single-center experience - Heise, Emma L.; Chichelnitskiy, Evgeny; Greer, Mark; Franz, Maximilian; Aburahma, Khalil; Iablonskii, Pavel; de Manna, Nunzio D.; Christoph, Stella; Verboom, Murielle; Hallensleben, Michael; Boethig, Dietmar; Avsar, Murat; et al. (American journal of transplantation, 2023)
Pretransplant allosensitization to human leukocyte antigens (HLA) increases the recipient’s waiting list time and mortality in lung transplantation. Rather than waiting for crossmatch-negative donors, since 2013, recipients with preformed donor-specific antiHLA antibodies (pfDSA) have been managed with repeated IgA- and IgM-enriched intravenous immunoglobulin (IgGAM) infusions, usually in combination with plasmapheresis before IgGAM and a single dose of antiCD20 antibody. This retrospective study presents our 9-year experience with patients transplanted with pfDSA. Records of patients transplanted between February 2013 and May 2022 were reviewed. Outcomes were compared between patients with pfDSA and those without any de novo donor-specific antiHLA antibodies. The median follow-up time was 50 months. Of the 1,043 patients who had undergone lung transplantation, 758 (72.7%) did not develop any early donor-specific antiHLA antibodies, and 62 (5.9%) patients exhibited pfDSA. Among the 52 (84%) patients who completed treatment, pfDSA was cleared in 38 (73%). In pfDSA vs control patients and at 8-year follow-up, respectively, graft survival (%) was 75 vs 65 (P = .493) and freedom from chronic lung allograft dysfunction (%) was 63 vs 65 (P = .525). In lung transplantation, crossing the preformed HLA-antibody barrier is safe using a treatment protocol based on IgGAM. Patients with pfDSA have a good 8-year graft survival rate and freedom from chronic lung allograft dysfunction, similar to control patients.